2013
DOI: 10.7554/elife.01501
|View full text |Cite
|
Sign up to set email alerts
|

A serine sensor for multicellularity in a bacterium

Abstract: We report the discovery of a simple environmental sensing mechanism for biofilm formation in the bacterium Bacillus subtilis that operates without the involvement of a dedicated RNA or protein. Certain serine codons, the four TCN codons, in the gene for the biofilm repressor SinR caused a lowering of SinR levels under biofilm-inducing conditions. Synonymous substitutions of these TCN codons with AGC or AGT impaired biofilm formation and gene expression. Conversely, switching AGC or AGT to TCN codons upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
133
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(142 citation statements)
references
References 49 publications
9
133
0
Order By: Relevance
“…3D, squares and triangles]) had much higher activities than the wild-type strain (YC952 [diamonds]). The reason why a mild decrease in the expression of sinR may lead to such a drastic increase in the expression of epsAepsO is due to hypersensitivity of SinR-mediated repression, a unique feature of SinR activity characterized in our previous studies (20,62).…”
Section: Fig 2 Colony and Pellicle Biofilms Formed By Mutants With Vamentioning
confidence: 99%
See 1 more Smart Citation
“…3D, squares and triangles]) had much higher activities than the wild-type strain (YC952 [diamonds]). The reason why a mild decrease in the expression of sinR may lead to such a drastic increase in the expression of epsAepsO is due to hypersensitivity of SinR-mediated repression, a unique feature of SinR activity characterized in our previous studies (20,62).…”
Section: Fig 2 Colony and Pellicle Biofilms Formed By Mutants With Vamentioning
confidence: 99%
“…Based on observations in our previous studies (61,62), in which spontaneous mutants bearing point mutations in either the sinR or abrB gene were shown to form both robust biofilms and extensive cell chains, we decided to map the suppressor mutation by trying the targeted approach first and sequencing those biofilm-related regulatory genes in the suppressor mutant. Interestingly, our sequencing results indeed revealed a single nucleotide substitution in a region immediately upstream of sinR.…”
Section: Fig 2 Colony and Pellicle Biofilms Formed By Mutants With Vamentioning
confidence: 99%
“…SinR is counteracted by a small antirepressor, SinI, whose expression is activated by a master regulator, Spo0A, under biofilm induction (13,14). More recently, we showed that metabolic signals also play important roles in triggering biofilm formation in B. subtilis (15)(16)(17). In one study, we discovered a novel serine-sensing mechanism that triggers biofilm formation by altering the translation efficiency of the biofilm repressor SinR in response to a decrease in cellular serine levels, which act as a proxy for the nutrient status in the bacterium (15).…”
mentioning
confidence: 98%
“…More recently, we showed that metabolic signals also play important roles in triggering biofilm formation in B. subtilis (15)(16)(17). In one study, we discovered a novel serine-sensing mechanism that triggers biofilm formation by altering the translation efficiency of the biofilm repressor SinR in response to a decrease in cellular serine levels, which act as a proxy for the nutrient status in the bacterium (15). In another study, acetic acid, a small volatile metabolite, was shown to stimulate biofilm formation in B. subtilis via air transmission (16).…”
mentioning
confidence: 99%
“…Profiling has proven to be increasingly valuable in studies of the translation process, for example, in the discovery of novel open reading frames (ORFs), the determination of elongation rates, the identification of sites of ribosome pausing and in the study of protein folding (for review, see Morris 2009;Weiss and Atkins 2011;Michel and Baranov 2013;Ingolia 2014;Jackson and Standart 2015). It also has broad application in the analysis of global gene expression and has been exploited in studies of infectious diseases (Stern-Ginossar et al 2012, 2015Liu et al 2013;Arias et al 2014;Caro et al 2014;Jensen et al 2014;Muzzey et al 2014;Vasquez et al 2014;Yang et al 2015), cell growth, differentiation and development Huang et al 2013;Lee et al 2013;Stadler and Fire, 2013;Stumpf et al 2013;Subramaniam et al 2013;Baudin-Baillieu et al 2014;Brubaker et al 2014;Duncan and Mata 2014;Gonzalez et al 2014;Hendriks et al 2014;Katz et al 2014;Kronja et al 2014;Schrader et al 2014;Vaidyanathan et al 2014;de Klerk et al 2015), apoptosis (Wiita et al 2013), mitochondrial gene expression and disease (Rooijers et al 2013;Williams et al 2014), cell stress (Gerashenko et al 2012;Labunskyy et al 2014;Zid and O'Shea 2014;Sidrauski et al 2015), cell toxicity …”
Section: Introductionmentioning
confidence: 99%